2009
DOI: 10.7326/0003-4819-151-6-200909150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Case Management for Depression by Health Care Assistants in Small Primary Care Practices

Abstract: German Ministry of Education and Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(141 citation statements)
references
References 50 publications
3
125
1
11
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 This cross-sectional study was nested in a trial on the effectiveness of case management from April 2005 to September 2007 for primary care patients with major depression. We included 74 practices and 626 patients (310 intervention recipients and 316 control patients) at baseline, and collected follow-up data from 84.2% of patients at 12 months (Gensichen et al, 2009a). The inclusion criteria for patients in the trial were: 1) diagnosis of major depression with indication for any antidepressive treatment; 2) age 18 to 80; 3) access to private telephone; 4) ability to give informed consent; 5) ability to communicate in German (Gensichen et al, 2005;Gensichen et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 3 This cross-sectional study was nested in a trial on the effectiveness of case management from April 2005 to September 2007 for primary care patients with major depression. We included 74 practices and 626 patients (310 intervention recipients and 316 control patients) at baseline, and collected follow-up data from 84.2% of patients at 12 months (Gensichen et al, 2009a). The inclusion criteria for patients in the trial were: 1) diagnosis of major depression with indication for any antidepressive treatment; 2) age 18 to 80; 3) access to private telephone; 4) ability to give informed consent; 5) ability to communicate in German (Gensichen et al, 2005;Gensichen et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…We included 74 practices and 626 patients (310 intervention recipients and 316 control patients) at baseline, and collected follow-up data from 84.2% of patients at 12 months (Gensichen et al, 2009a). The inclusion criteria for patients in the trial were: 1) diagnosis of major depression with indication for any antidepressive treatment; 2) age 18 to 80; 3) access to private telephone; 4) ability to give informed consent; 5) ability to communicate in German (Gensichen et al, 2005;Gensichen et al, 2009a). The diagnosis of major depression was based on a score of more than 9 points and a categorical diagnosis in the Patient Health Questionnaire-9 (PHQ-9) (Kroenke et al, 2001), and was confirmed by the family physician by using the checklists in the International Classification of Diseases 10.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of this study is that it is the fi rst to examine the implementation of case management in small-scale primary practices, 6 as well as the perception of the HCA in this specifi c setting. It seems that the focus on a single perspective of this topic-the perspective of the HCAs-is both a strength and a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…The trial examined the effect of case management for patients with major depression compared with usual care in small primary care practices. 6 A practice-based HCA monitored patients by means of a monthly telephone call using the Depression Monitoring List to assess patients' depression symptoms and medication adherence. 15 Results were reported to the family physician and, if necessary, discussed by the family physician and the HCA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation